PENERAPAN METODE PROSENTASE PENYELESAIAN DALAM RANGKA PENGAKUAN PENDAPATAN PADA PERUSAHAAN JASA KONTRAKTOR: (Studi kasus di PT ‘X’ Surabaya) - Diana Zuhroh (Fakultas Ekonomi Universitas 45 Surabaya, 2014)
PT “X” is engaged in contracting services, where in term of recognition of revenues and expenses are based on the stage of completion that was determined based on observations by the implementer section directly to the project that being carried out (physically). Based on the data obtained, for solving the problem, researchers used method of completion percentage that was calculated as the proportion of contract costs for the works that performed to the date of the total estimated cost of contract (in accordance with PSAK No. 34), where for the calculation of the completion stage and recognition of revenues, the material purchases are recorded as inventories and recognized as expenses upon the use of it. After processed it turns out there is a revenue correction of Rp.614,079,534.43 of which is the addition to income for the year 2012 and a reduction in revenues in 2013. Similarly about the cost, there are correction for Rp.55,595,650 which is a costs reduction tor 2012 and additional cost to 2013. Before the correction, in 2012 the company suffered a loss of Rp. 141,323,669 and after the correction actually gets a profit of Rp. 110,221,843. Thus the determination of completion stage that based on the observation of the implementer section can not be used as a basis to recognize contract revenue, especially for the contract that more than one accounting period, because the revenues and costs are not proportional.